Is there a vet in the house? - New Sunday Times, Koh Soo Ling (2004)
If you love animals and feel a genuine commitment to their well-being, the veterinary science is worth pursuing. Aspiring veterinarians must possess a high academic ability, an aptitude and interest in biological sciences, an inquiring mind, keen powers of observation and good communication skills.